Flice-Inhibitory protein is a key regulator of germinal center B cell apoptosis - Hennino, Ana; Krammer, Peter H. (Journal of experimental medicine, 2001)
Affinity maturation of the B cell response to antigen (Ag) takes place in the germinal centers (GCs) of secondary follicles. Two sequential molecular mechanisms underpin this process. First, the B cell repertoire is diversified through hypermutation of the immunoglobulin (Ig) variable region genes. Second, mutant B cell clones with improved affinity for Ag are positively selected by Ag and CD40 ligand (L). This selection step is contingent upon “priming” of GC B cells for apoptosis. The molecular means by which B cell apoptosis is initiated and controled in the GC remains unclear. Here, we show that GC B cell apoptosis is preceded by the rapid activation of caspase-8 at the level of CD95 death-inducing signaling complex (DISC). We found that GC B cells ex vivo display a preformed inactive DISC containing Fas-associated death domain-containing protein (FADD), procaspase-8, and the long isoform of cellular FADD-like IL-1β-converting enzyme-inhibitory protein (c-FLIPL) but not the CD95L. In culture, c-FLIPL is rapidly lost from the CD95 DISC unless GC B cells are exposed to the survival signal provided by CD40L. Our results suggest that (a) the death receptor signaling pathway is involved in the affinity maturation of antibodies, and (b) c-FLIPL plays an active role in positive selection of B cells in the GC.